2012
DOI: 10.1186/1471-2164-13-233
|View full text |Cite
|
Sign up to set email alerts
|

A defect in dystrophin causes a novel porcine stress syndrome

Abstract: BackgroundLosses of slaughter-weight pigs due to transport stress are both welfare and economic concerns to pork producers. Historically, the HAL-1843 mutation in ryanodine receptor 1 was considered responsible for most of the losses; however, DNA testing has effectively eliminated this mutation from commercial herds. We identified two sibling barrows in the USMARC swine herd that died from apparent symptoms of a stress syndrome after transport at 12 weeks of age. The symptoms included open-mouth breathing, sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 40 publications
4
37
0
2
Order By: Relevance
“…Several animal models of the disease exist, including the dystrophin-deficient mdx mouse [77, 78], and feline [79] and canine X-linked models of muscular dystrophy [80-90]. Dystrophin deficiency affecting cardiac and skeletal muscle has also been described in swine [91] but little information has been published regarding the causal mutation and the associated phenotype.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Several animal models of the disease exist, including the dystrophin-deficient mdx mouse [77, 78], and feline [79] and canine X-linked models of muscular dystrophy [80-90]. Dystrophin deficiency affecting cardiac and skeletal muscle has also been described in swine [91] but little information has been published regarding the causal mutation and the associated phenotype.…”
Section: Animal Modelsmentioning
confidence: 99%
“…However, there has been a newly identified mutation in the dystrophin gene which leads to loss of animals due to transport stress, and pathological findings are similar to porcine stress syndrome (Nonneman et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Genotypic analyses have indicated that the mutation arose from a single founder animal. However, a newly identified mutation (R1958W) in the dystrophin gene has recently been shown to be responsible for loss of animals due to transport stress (Nonneman et al, 2012). The mode of inheritance is autosomal recessive with variable penetrance.…”
Section: Porcine Stress Syndromementioning
confidence: 99%
“…Lesions in animals with the dystrophin mutations consist of cardiomyofiber degeneration (Nonneman et al, 2012). In addition, many of the animals will have muscles that appear very pale and are very soft, almost watery in texture, due to the high lactic acid content in muscles that occurs postmortem.…”
Section: Porcine Stress Syndromementioning
confidence: 99%